The Effectiveness of Problem Based Learning-Based Interactive Multimedia for Elementary School Students - Sekarwangi, Tunjung; Sartono, Kus Eddy; Mustadi, Ali; Abdulah, Abdulah (Universitas Pendidikan Ganesha, 2021)
Learning activities carried out online have several drawbacks. In online learning activities, teachers experience problems carrying out learning activities. These obstacles include the lack of appropriate media to be used in learning activities. The problems that occur indicate that in learning activities students have difficulty in understanding learning materials and learning motivation is still low. Therefore, in learning activities, teachers must prepare quality learning. One of the efforts that can be done to overcome these problems is through the use of appropriate learning media. So that it can improve the process and better learning outcomes. This study uses a research and development (R&D) approach. The purpose of this research is to develop learning technology in the form of interactive multimedia based on problem-based learning. The steps used in this research and development is the ADDIE development model. The research data was obtained through a media validation sheet instrument by an expert. Data analysis was carried out quantitatively descriptively. The results of the media feasibility test based on the validation results obtained a value of 80%. Based on the results of the research that has been done, it can be concluded that interactive multimedia based on problem-based learning is feasible to be used in learning activities. The results of this study imply that the use of interactive multimedia based on problem-based learning plays an important role in the effectiveness of learning activities.